Failure of single‐unit restorations on root filled posterior teeth: a systematic review. (17th January 2017) - Afrashtehfar, K. I.; Ahmadi, M.; Emami, E.; Abi‐Nader, S.; Tamimi, F.
Abstract: This systematic review investigated the failure rate of conventional single‐unit restorations in root filled posterior permanent teeth. Two reviewers independently applied eligibility criteria, extracted data and assessed the quality of the evidence of each included study according to the Cochrane Collaboration's procedures for randomized control trials (RCTs) and the STROBE criteria for observational studies. The MEDLINE (via Ovid), EMBASE (via Ovid), Cochrane Oral Health Group Trials Register and CENTRAL (via Cochrane Library) databases were searched electronically (January 1993 to week 1, February 2015). This was complemented by an additional hand search of selected journals and the references of relevant studies. Clinical studies published on root filled single‐unit restorative treatments with a mean follow‐up period of at least 3 years were selected. The outcome measured was clinical or radiological failure. Overall, the four RCTs and the single observational study included were of low and high quality, respectively. Therefore, a meta‐analysis was not possible. The pooled mean failure rates were reported according to the type of treatment and remaining coronal tooth structure. The current evidence suggested that the failure rates of the treatments may depend on the amount of remaining tooth structure and type of treatment. Post‐retained crowns were associated with the most favourable outcome in teeth with one to two remaining coronal tooth wall(s), whereas post‐free crowns were superior when greater tooth structure was available. Restorations in teeth without ferrules had such a high rate of failure that other treatment options should be considered.